The Unified Theory of Acceptance and Use of Technology (UTAUT) in higher education: a systematic review - Xue, Liangyong; Mat Rashid, Abdullah; Ouyang, Sha (SAGE Publications, 2024)
This systematic review evaluates the application of the Unified Theory of Acceptance and Use of Technology (UTAUT) model in higher education, analyzing 162 SSCI/SCI-E articles from 2008 to 2022. It reveals a predominant focus on student participants from Asia and North America. Mobile learning tools are the most studied technologies. Surveys continue to be the top data gathering method, while structural equation modeling is preferred for analysis. The Technology Acceptance Model is combined most with UTAUT. UTAUT testing shows performance expectancy has the strongest sway on behavioral intention. Additionally, the review underscores nuanced variances in the impact of UTAUT factors between higher education and general contexts. The study calls for future UTAUTapplications must promote inclusive research spanning diverse groups, mixed methodologies and theoretical perspectives. This comprehensive approach is imperative to fully understand technology adoption patterns in higher education and enable context-specific integration strategies.